DETERMINANTS OF CORPORATE VALUE: SUSTAINABILITY REPORTING, INTELLECTUAL CAPITAL AND GOOD CORPORATE GOVERNANCE IN MANUFACTURING COMPANIES IN INDONESIA - Nurul Aini; Lilik Pirmaningsih; Novaldy Arief Pradika; Elizabeth Dellysiana; Ratna Madudari (ZILLZELL MEDIA PRIMA, 2024)
This study aims to test and analyze the influence of sustainability reporting, intellectual capital and good corporate governance on company value. The sample used in the study is manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2023 period as many as 87 years of companies, Data analysis using SPSS 25. The results of this study show that sustainability reporting, intellectual capital and good corporate governance proxied by the audit committee and independent commissioners have a significant effect on the company's value.